#TITLE_ALTERNATIVE# - ZAENAL ABIDIN (NIM : 13107065); Pembimbing Utama : Dr. Ir. Zainal Abidin, ALI
Hydrodynamic journal bearing is a bearing capable of supporting radial load using hydrodynamic lubrication. This type of bearing is often used in rotating machinery; especially for rotating machinery with heavy load and high rotational speed. During operation, hydrodynamic journal bearing sometimes encounters problems. Because of that, the dynamic characteristics of this type of bearing need to be studied in detail. For this purpose, a rotor shaft system, supported by hydrodynamic bearings, has been made in the Dynamic Laboratory PAU-ITB. However, the characteristics of this system is not yet fully studied because the experiment that has been done so far does not show the shaft lifting phenomena due to hydrodynamic force. In this final project, an experiment would be performed to investigate the shaft lifting phenomena due to the hydrodynamic forces. To investigate the phenomena, average shaft centerline and orbit measurements were performed. This process is done by data recording. For average shaft centerline measurement, the recording process uses DC coupling measurement while for orbit measurement, the recording process uses AC coupling so. The data taken from this measurements are DC average and AC RMS values. DC average values describe shaft motion inside the bearing, while AC RMS value describes shaft vibration level inside the bearing. This measurement is done by varying the rotational speed as well as lubrication viscosity. There were two types of lubrication, used in this research, ISO VG32 and ISO VG68. The results of the experiment which had been done with ISO VG32 and ISO VG68 show that shaft rotor system is moving up as it rotate. Using ISO VG32, the rotor shaft system begins move up at rotational speed below 1.200 rpm. While with ISO VG68,the rotor shaft system begins move up at rotational speed below 480 rpm.